THE ROLE OF THE MACROORGANISM IN THE MANIFESTATION OF PATHOGENIC PROPERTIES IN CONDITIONAL PATHOGENIC MICROFLORA - Ma’murova Iroda,; Kudratova Z.E., (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Some normal microorganisms in the macroorganism can cause subclinical and clinical manifestations of infectious diseases under certain conditions. Therefore, today there is a need for a more detailed study of microorganisms themselves, the conditions that lead to the occurrence of infectious diseases with the participation of these microorganisms, improvement of methods of diagnosis, treatment, and prevention [1,2,3].